Does a kangaroo have a mother, too? - Carle, Eric. (New York Scholastic, 2000)
Presents the names of animal babies, parents, and groups, for example, a baby kangaroo is a joey, its mother is a flyer, its father is a boomer, and a group of kangaroos is a troop, mob, or herd.
190
F
Keywords: Animals -- Infancy -- Juvenile literature; Animals -- Infancy